Online love fraud and the experiences of indonesian women: a qualitative study - Niman, Susanti; Parulian, Tina Shinta; Rothhaar, Timothy (International Journal of Public Health Science (IJPHS), 2023)
Online love fraud is a cybercrime. Victims typically lose around 500 billion rupiahs every year in Indonesia. The research related to the experiences of victims of love scammers is limited, and the authorities often ignore victims who report. This study aimed to explore the experiences of Indonesian women as a victim. The study is qualitative with a phenomenological design utilizing purposive sampling. Twelve victims of online love fraud participated in the study. Data was collected through semi-structured interviews via video chat. Data processing was carried out by verbatim transcription of the video chats. The resulting texts were then rigorously read and re-read, coded, and grouped according to emerging themes. The victims described the experiences of sending large sums of money and naked photos to the perpetrators. The themes reflect the psychosocial impact of love fraud on women: shock, sadness, anger, low self-esteem, anxiety, depression, and suicidal thoughts. Online love fraud impacts the psychosocial functioning of victims. Victims feel a double burden in losing money and self-respect. These findings highlight the importance of policy, mental health practice, and research. Conclusions suggest psychosocial intervention is vital for the survivor.